Juvinall's fundamentals of machine component design SI version - Juvinall, Robert C.; Marshek, Kurt M. (John Wiley & Sons, Inc., 2017)
Valued as a standard in the course, Juvinall's Fundamentals of Machine Component Design continues to focus on the fundamentals of component design - free body diagrams, force flow concepts, failure theories, and fatigue design, with applications to fasteners, springs, bearings, gears, clutches, and brakes. Problem-solving skills are developed by the implementation of a proven methodology which provides a structure for accurately formulating problems and clearly presenting solutions. This edition includes additional coverage of composites, the material selection process, and wear/wear theory, along with new and updated examples and homework problems